A new model for bridge management: Part A: condition assessment and priority ranking of bridges. Issue 1 (1st January 2016) - Rashidi, Maria; Samali, Bijan; Sharafi, Pezhman
Abstract: Due to substantial role of bridges in transportation networks and in accordance with the limited funding for bridge management, remediation strategies have to be prioritised. A conservative bridge assessment will result in unnecessary actions, such as costly bridge strengthening or repairs. On the other hand, any bridge maintenance negligence and delayed actions may lead to heavy future costs or degraded assets. The accuracy of decisions developed by any manager or bridge engineer relies on the accuracy of the bridge condition assessment which emanates from visual inspection. Most of the bridge ranking systems are commonly based on structural condition. Parameters such as functionality and client preferences are used in an isolated fashion. The developing prioritisation method described herein is an important step in adding more holism and objectivity to the current approaches. To achieve this goal, all important parameters have been identified, weighted and finally synthesised in an index introduced as Priority Index (PI). PI is expressed as a number which enables the decision-makers to simply understand and compare the overall condition of a variety of bridges in the network. It embraces three factors: structural efficiency, functional efficiency and client impact factor. The proposed model was tested through case studies and qualified experts (senior bridge inspectors, engineers and asset managers) from about 30 private and public transportation authorities.